Systematic qualitative proteome-wide analysis of lysine malonylation profiling in Platycodon grandiflorus - Qingshan Yang; Shaowei Xu; Weimin Jiang; Fei Meng; Shuting Wang; Zongping Sun; Na Chen; Daiyin Peng; Juan Liu; Shihai Xing (Amino Acids)
Abstract In recent years, it was found that lysine malonylation modification can affect biological metabolism and play an important role in plant life activities. Platycodon grandiflorus, an economic crop and medicinal plant, had no reports on malonylation in the related literature. This study qualitatively introduces lysine malonylation in P. grandiflorus. A total of 888 lysine malonylation-modified proteins in P. grandiflorus were identified, with a total of 1755 modification sites. According to the functional annotation, malonylated proteins were closely related to catalysis, binding, and other reactions. Subcellular localization showed that related proteins were enriched in chloroplasts, cytoplasm, and nuclei, indicating that this modification could regulate various metabolic processes. Motif analysis showed the enrichment of Alanine (A), Cysteine (C), Glycine (G), and Valine (V) amino acids surrounding malonylated lysine residues. Metabolic pathway and protein-protein interaction network analyses suggested these modifications are mainly involved in plant photosynthesis. Moreover, malonylated proteins are also involved in stress and defense responses. This study shows that lysine malonylation can affect a variety of biological processes and metabolic pathways, and the contents are reported for the first time in P. grandiflorus, which can provide important information for further research on P. grandiflorus and lysine malonylation’s role in environment stress, photosynthesis, and secondary metabolites enrichment.